Processing, Quality, Safety, and Acceptance of Meat Analogue Products - Cuixia Sun; Jiao Ge; Jun He; Renyou Gan; Yapeng Fang (Engineering, 2021)
Rapid global population growth has caused an increasing need for products containing protein. Meat products are the most common high-protein food source, but impact the environment, cause animal welfare issues, and raise public health concerns. Consumer health and food safety are paramount to the food industry. Both the scientists and food industry are actively seeking plant proteins to substitute for animal-sourced proteins. Plant proteins have a well-balanced amino acid composition, and exhibit great potential for replacing meat via the development of healthy, high-protein, low-saturated fat, cholesterol-free, and nutritionally similar meat-like products. Generally, meat analogue formulations are specially designed and processing conditions are optimized to obtain the texture and bite of real animal meat. This article focuses on plant-based meat analogues, and covers aspects regarding processing, products, quality, and nutritional and structural modifications. Product safety consciousness and consumer acceptance are also discussed. Challenges and perspectives for future research concerning nonmeat products are presented.